دراسة الخصائص الإحصائية لتوزيعات درجات تلاميذ الحلقة الأولى من مرحلة التعليم الأساسي في محافظتي دمشق و ريف دمشق - درويش، رمضان محمد; رضوان، رانيه جميل (جامعة البعث, 2011)
هدف هذا البحث إلى تحليل درجات تلاميذ الحلقة الأولى من مرحلة التعليم الأساسي في محافظتي دمشق وريف دمشق، والكشف عن الخصائص الإحصائية لتوزيعات درجاتهم، وإن كانت تختلف بين مجموع محصلات الفصل الدراسي الأول ومجموع محصلات الفصل الدراسي الثاني، وباختلاف المحافظة. تألفت عينة البحث من درجات (2601) تلميذا وتلميذة تم اختيارهم بطريقة عشوائية طبقية من بين التلاميذ الذين تقدموا لاختبارات الفصلين الدراسيين الأول والثاني من العام الدراسي 2009/2010م، واتبعت الباحثة المنهج الوصفي التحليلي للإجابة عن أسئلة البحث، وتم إجراء عدد من التحليلات الإحصائية تمثلت بحساب مقاييس النزعة المركزية (المتوسط والوسيط والمنوال والانحراف المعياري والالتواء والتفرطح، وتمثيل درجات التلاميذ المختلفة في أشكال بيانية تتمثل في المدرج التكراري والمنحنى الطبيعي. من أهم نتائج البحث؛ \ 1-\ أظهر تحليل بيانات النتيجة العامة ومجموع محصلات الفصل الدراسي الأول ومجموع محصلات الفصل الدراسي الثاني أن جميع التوزيعات تميل نحو الالتواء السلبي. \ 2-\ كما أظهر تحليل النتائج على أن هناك: \ -\ ارتفاع ملحوظ في قمة توزيع درجات تلاميذ محافظة دمشق عن قمة التوزيع الطبيعي من جهة، وقمة توزيع درجات تلاميذ محافظة ريف دمشق من جهة أخري. \ -\ ارتفاع درجات التلاميذ في الفصل الدراسي الثاني عن درجاتهم في الفصل الدراسي الأول. The objective of this research is to analyze the grades of the first grade of basic education in the governorates of Damascus and Damascus countryside, and reveal the statistical properties of the distributions of grades, and if they differ between the total outcomes of the first semester and the total outcomes of the second semester, and according to the governorate. The research sample consisted of (2601) pupils´ degrees were selected by stratified random method from among pupils who have applied for tests semesters I and II of the academic year 2009/2010, the researcher followed the descriptive analytical approach to answer the research questions, a number of statistical analysis was used that were Central tendency measures (mean, median and mode), standard deviation, skewness and kurtosis, and the representation of pupils´ different grades in the graphs represented in the histogram and normal curve. \ The most important research results were: \ 1\ - Data analysis of the overall result , the total outcomes of the first semester and the total outcomes of the second semester appeared that all the distributions tend towards the negative skewness. \ 2\ - Analysis of the results appeared that there is: \ - A significant increase at the top of the distribution of pupils´ degrees of the governorate of Damascus from the top of the normal distribution on the one hand, and the top of the distribution of pupils´ degrees of the governorate of Damascus countryside on the other hand. \ – Raise in pupils´ degrees in the second semester more than their degrees in the first semester.
Keywords: التعليم الأساسي -- التلاميذ -- التحصيل الدراسي -- الدراسات الإحصائية -- سوريا